Evaluation of a Chromosome Segment from Gossypium barbadense Harboring the Fiber Length QTL qFL‐Chr.25 in Four Diverse Upland Cotton Genetic Backgrounds. Issue 6 (1st November 2019) - Brown, Nino; Kumar, Pawan; Singh, Rippy; Lubbers, Ed; Campbell, B. Todd; Myers, Gerald O.; Wright, Robert J.; Subramani, Jay; Jones, Don; Paterson, Andrew H.; Chee, Peng W.
ABSTRACT: Competition with manmade fibers has increased focus on upland cotton ( Gossypium hirsutum L.) fiber quality, especially upper half mean length (FL), for industry stakeholders and breeders. The purpose of this study was to characterize the effect of qFL‐Chr.25, a quantitative trait locus (QTL) introgressed from G. barbadense L. originally identified in 'Sealand 883'. The QTL was deployed within four genetic backgrounds: Acala SJ4, Paymaster HS26, Deltapine 50 (DP 50), and Georgia 2004089 (GA089), each representing the gene pools of the major US cotton‐growing regions: the US Southwest, Texas High Plains, Mississippi Delta, and US Southeast, respectively. In highly related bulked sister lines (BSLs), the effect of qFL‐Chr.25 was significant in the DP 50 (1.4 mm) and GA089 (1 mm) backgrounds in trials grown in Tifton, GA, in 2014 and 2015. In multilocation trials planted across the Cotton Belt in 2011 of 25 lines from each of the four backgrounds carrying the G. barbadense allele and 25 without the introgressed allele, FL of the QTL(+) lines were numerically higher than the QTL(−) lines by 0.9 mm, though not statistically significant. Recombinant genotypes recovered from the Paymaster HS26 and GA089 backgrounds, and development of additional simple sequence repeat (SSR) markers within the QTL region, allowed further refinement of the qFL‐Chr.25 region's boundaries from ∼2.2 to 0.8 Mb. Although variable effects were seen from this QTL, observation in a more isogenic state such as the BSLs and recombinant lines made the effect of the QTL more apparent. Incorporation of this QTL into breeding programs aided by these newly developed SSR markers should help in the utilization of this introgression to improve cotton fiber quality.